2015
DOI: 10.1111/rode.12127
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomic Volatility, Institutional Instability and the Incentive to Innovate

Abstract: This study investigates the channels through which macroeconomic and institutional instability hinders innovative investment undertakings financed by the domestic private sector. The analysis is based on a sample of 44 countries and considers various instability dimensions. The results suggest a negative impact of real, monetary and political instability on the aggregate level of R&D financed by the business sector. Thus, highlighting the importance of stable macro‐institutional environments in preventing avoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
(58 reference statements)
0
5
0
3
Order By: Relevance
“…Instability in the political condition gives rise to the possibility of frequent changes or cancellation of those short and long run policies and creates economic uncertainty and therefore affect the R&D investment. A number of authors have found that political instability negatively affects the level of R&D investment including Henisz (2002), Allard et al (2012), and Masino (2015). As the volatility and uncertainty caused by political uncertainty are significantly higher in emerging markets as suggested by Easterly et al (2000) and Klomp and Haan (2009), this study is proposing following hypothesis:…”
Section: Theory and Hypothesesmentioning
confidence: 67%
See 1 more Smart Citation
“…Instability in the political condition gives rise to the possibility of frequent changes or cancellation of those short and long run policies and creates economic uncertainty and therefore affect the R&D investment. A number of authors have found that political instability negatively affects the level of R&D investment including Henisz (2002), Allard et al (2012), and Masino (2015). As the volatility and uncertainty caused by political uncertainty are significantly higher in emerging markets as suggested by Easterly et al (2000) and Klomp and Haan (2009), this study is proposing following hypothesis:…”
Section: Theory and Hypothesesmentioning
confidence: 67%
“…Therefore, any instability in political condition will affect R&D more than other forms of corporate investments. Masino (2015) pointed out that in an uncertain and volatile economy, firms tend to reduce the level of investment in innovative activities. Atanassov et al (2016) argued that uncertainty increases the value of option to wait before making investments.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…What factors will influence enterprises' innovation on research and development? Previous research has found that influential factors of research and development include external economic and political environments [10], such as macroeconomic volatility [11], interest rate marketization [12], political instability [13], judicial system [14], and the nature of business [15]. However, according to many studies since the innovation theory was proposed by Joseph Schumpeter, enterprises do not focus on external influencing factors only.…”
Section: Introductionmentioning
confidence: 99%
“…En el caso de los factores políticos y macroeconómicos, la corrupción sugiere un impacto negativo en la actividad innovadora de las empresas (Xu y Yano 2016;Paunov, 2016;Goedhuys, Mohnen y Taha 2016; Barasa, 2018; Pirtea, Sipos e Ionescu, 2019). La inestabilidad política manifiesta un impacto negativo en la I+D y obstaculiza el intercambio del conocimiento y la innovación (Allard, Martínez y Williams, 2012;Masino, 2015). Sin embargo, es menos grave entre los empresarios que tienen conexiones políticas y aseguran el apoyo gubernamental para la inversión en innovación (Cumming, Rui y Wu, 2016).…”
Section: Revisión De La Literaturaunclassified
“…En el caso de las empresas del sector manufacturero argentino que innovan en el producto, se evidencia mayor probabilidad de presentar como barrera la inestabilidad política, que coincide con la investigación de Masino (2015) en su estudio en países miembros de la OCDE, y en la innovación en el proceso destacan el crimen, el robo y el desorden. Con menor propensión se evidencia en empresas argentinas que innovan en el producto barreras como el acceso al financiamiento, las regulaciones laborales y la fuerza de trabajo con educación inadecuada; estas limitaciones coinciden con hallazgos de investigaciones realizadas en Argentina (Guercio et al, 2014;WEF, 2016;Arza y López, 2018;Petelski et al, 2019).…”
Section: Conclusiones E Implicacionesunclassified